Enhancing psychological well-being of school teachers in India: role of energy management, thriving, and stress - Chaudhry, Smita; Chhajer, Raina (Frontiers in Psychology, 2023)
Purpose: The psychological well-being of school teachers is a growing concern in the post-pandemic era. Many initiatives are undertaken by individual school authorities and government agencies to address this issue. In this study, we examine the impact of energy management, thriving, and stress on the psychological well-being of school teachers in India. Method: Data was collected from 356 school teachers in Rajasthan, India, through a cross-sectional questionnaire. These teachers were working both in rural and urban areas. The relationship among energy management, thriving, stress, and psychological well-being was analyzed using hierarchical regression. Results: The findings suggest that energy management positively impacts psychological well-being. A mediating effect of thriving and stress on the relationship between energy management and psychological well-being was also found. The results support that psychological well-being can be enhanced by investing in managing school teachers' energy levels. Discussion: The paper is unique in understanding the role of energy management, thriving, and stress in enhancing the psychological well-being of school teachers. Keywords: energy management; India; psychological well-being; school teachers; stress; thriving